Culture, Gender and Spatial Arrangement in Traditional Houses - Dara Wisdianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Culture is always related to all aspects of daily life.  Culture can be either abstract or concrete, as a result of human behavior to respond to its environment. House is a physical manifestation of the inhabited tradition that made by human because they are aware that not all of their activities can be carried out in the open air. Because of the close relation with the prevailing culture, the form of housing which is being represented as the form of space reflects the cultural that is adopted by its occupants. The inhabited tradition poses a different culture in each region. It has its own tradition that brings to the surface multiplicity of gender definition that has an impact on the arrangement of living space in each house. Gender is very influential in spatial arrangement in traditional houses. Seen from the domination of men and women in certain rooms as well as understand the duality at some parts of the house.  The gender differences that exist in traditional houses have different backgrounds, ranging from the existing religious system, family patterns, and the use of local customs. This journal will explain the meaning of culture, gender, and housing, the relationship between the three and how they affect the spatial arrangement of traditional houses.